Експресiя генiв δ-циклiнiв у кореневiй меристемi проросткiв гороху (Pisum sativum L.) за умов клiностатування - Артеменко, О.А.; Кордюм, Є.Л. (Видавничий дім "Академперіодика" НАН України, 2007)
By the methods of hybridization in situ and RT-PCR, we show, for the ﬁrst time, the expression of genes of δ1- and δ3-cyclins in cells of the root meristem of pea (Pisum sativum L.) under slow horizontal clinorotation and stationary conditions of growing. We detect the clinorotation effect on the expression of genes of δ3-cyclin after 24 h of the wetting of seeds. The presence of transcripts of this cyclin can be a cause for the prolongation of G1-G1/S phases and, as a result, for the delay of the beginning of DNA replication in this period.